An optimized LQG servo controller design using LQI tracker for VSP-based AC/DC interconnected systems. (July 2021) - Rakhshani, Elyas; Naveh, Iman Mohammad Hosseini; Mehrjerdi, Hasan; Pan, Kaikai
Highlights: The first study on high-level control strategy for VSP-based AC/HVDC systems. A global feedback law for coordination between VSP station and rest of AC/DC system. A modified LQG servo controller tuned by swarm-based algorithm for VSP-based system. Analysis of modified LQG controller for VSP-based HVDC system in the presence of noises. Validated effectiveness of the control on in state estimation and reference tracking. Abstract: This paper proposes a novel application for the optimal Linear Quadratic Gaussian (LQG) servo controller to enable a proper coordination of the AC/HVDC interconnected system with Virtual Synchronous Power (VSP) based inertia emulation. Particularly, the proposed control design takes the process disturbances and measurement noise of the studied VSP-HVDC system into account, while few studies have focused on this perspective. The proposed LQG controller with modifications is designed by means of a combination of Kalman Filter (state estimator) and an added Linear Quadratic Integrator (LQI) to observe the system model's states and track the reference commands while rejecting the effects of system noise. Besides, we utilize a swarm-based optimization algorithm to operate as the search process for the tuning of the elements in the weighting matrices involved in the controller design. The role of the proposed optimal LQG controller is to stabilize such AC/DC interconnected system with VSP-based inertia emulator while minimizing the associated performance index. According to the obtained simulation results, in addition to the advancement from the VSP-based approach for damping frequency oscillations excited by faults, application of the proposed LQG servo controller can achieve the targets on both estimating the state variables and tracking the reference signals with satisfactory performance, comparing with the conventional LQG regulator.